Pengaruh Produk Wisata Terhadap Keputusan Berkunjung Wisatawan Pada Wonderland Adventure Waterpark Karawang - Eka Diah Apriliani; Mutia Mardhatillah; Alifia Syafa Ardinezwari; Abdul Yusuf (Sains: Jurnal Manajemen dan Bisnis, 2022)
This research aims to obtain empirical evidence about the influence of tourism product to tour visiting decision on Wanderland Adventure Waterpark Karawang. This analysis using independent variabel is tourism product and dependent variabel is tour visiting decision. This is quantitative research that distributes data and questionnaires. Samples in this research were the tourist of Wonderland Adventure Waterpark Karawang and the sampling technique used simple random sampling with a total sample of 204 re-spondens. Data analysis techniques use simple linear regression by using SPSS 22. This research proves that tourism product have significant influence to tourist visiting decision. From the result, this research can be useful as knowledge and consideration for tourist attractions manager in improving quality to attract tourist visitors.